CARACTERIZAÇÃO FÍSICO-QUÍMICA DE MELANCIA 'QUETZALI' DURANTE O DESENVOLVIMENTO - MARIA LUCILÂNIA BEZERRA DE ALMEIDA; GEOMAR GALDINO DA SILVA; RAILENE HÉRICA CARLOS ROCHA; PATRÍCIA LÍGIA DANTAS DE MORAIS; JOSÉ DARCIO ABRANTES SARMENTO (Revista Caatinga, 2010)
At present, the preference of the internal and external markets is for small fruits. Therefore the size, other aspects equally are important and considered to determining harvest point how soluble solids, coloration and format. The objective of the present work was determined the physical-chemical changes during the development of watermelon 'Quetzali' with support for the harvest in the size demanded by the extern market. Six harvests were made, the first occasion of marks made on fruits with fresh weight of 2 g and the other at 10, 15, 20, 15 and 30 days of development. Next, the fruits were transported for the laboratory of Irrigated Agriculture of the UFERSA, in Mossoró-RN-Brazil. The experiment was installed in design entirely at random composed by five treatments (days of development), five replications and a fruit for replication. Fresh mass was analysed (g), growth rate of the fruit (g.day-1), length and diameter of fruit (cm), firmness of the pulp (N), vitamin C (mg.100 mL-1 ascorbic acid), soluble solids (SS, %) and titratable acidity (AT, g.100 mL-1 acid malic). The watermelon variety Quetzali obtained the very growth rate of 178.64 g to 20 days and the very diameter of 19.57 cm to 25 days, when size adapted for harvest. To 25 days of development the fruits had firmness of pulp 15 N, soluble solids 8.9%, titratable acidity 0.1289 mg.100 mL-1 acid malic and vitamin C 7.3 mg.100 mL-1 ascorbic acid.